Choques a la cuenta corriente de la balanza de pagos: Alguna evidencia para Argentina - Luis N. Lanteri (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2018)
– The aim of this paper is to identify the different shocks that could affect the current account in the argentine case, such as the terms of trade (the Harberger-Laursen-Metzler effect-HLM), supply shocks (productivity), demand shocks (real exchange rate and public consumption /current GDP) and the shocks on the production side of the economy. SVAR models with long-term restrictions and quarterly data covering the period 1994-2018 are used. The results of the impulse-response functions suggest the existence of the HLM effect for this country. Shocks in the terms of trade would initially affect to the current account positively, as the improvements in the productivity and in the public saving (lower consumption).
Keywords: C3; E62; F32; F41; 330; current account; terms of trade; Harberger-Laursen-Metzler (HLM) effect; productivity; public consumption; SVAR models